2005
DOI: 10.1111/j.1468-2958.2005.tb00874.x
|View full text |Cite
|
Sign up to set email alerts
|

How Attention Partitions Itself During Simultaneous Message Presentations

Abstract: Television producers, across all types of programming, assume young viewers can parallel process simultaneously presented messages. For instance, television news producers appear to believe that young viewers can attend to weather icons, lexical news crawls, and sports scores while they also attend to news anchors who present the news. Nonetheless, attention theory suggests parallel processing on this scale cannot be executed effi ciently. Given the format's popularity, perhaps those messages take advantage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…To process these simultaneous stimuli requires multitasking. Such formats are very popular with younger viewers (ages 18 to 34), whereas older viewers (over 55) dislike them most (41,42). Nonetheless, the distracting information exacts a cognitive cost, even from the younger generation who have had more experience with multitasking.…”
Section: Technology and Multitasking: Benefits And Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…To process these simultaneous stimuli requires multitasking. Such formats are very popular with younger viewers (ages 18 to 34), whereas older viewers (over 55) dislike them most (41,42). Nonetheless, the distracting information exacts a cognitive cost, even from the younger generation who have had more experience with multitasking.…”
Section: Technology and Multitasking: Benefits And Costsmentioning
confidence: 99%
“…A controlled experiment showed that college students recalled significantly fewer facts from four main news stories in CNN's visually complex environment than from the same stories presented in a visually simple format, with the news anchor alone on the screen and the news crawls etc. edited out (41).…”
Section: Technology and Multitasking: Benefits And Costsmentioning
confidence: 99%
“…In spite of this evidence that simultaneous presentation of congruent verbal and pictorial information is a highly effective way to transmit information, it is also clear that there are processing limits which may be reached or exceeded with too much incongruent or unrelated information in simultaneous channels, as seen in the complex cluttered formats of some cable news channels (Bergen, Grimes, & Potter, 2005) Another concern is that redundant or incomprehensible information in multiple channels is not only no help in comprehension but in fact is a distraction that interferes with learning. For example, Lavaur and Bairstow (2011) found that subtitles, either in one's own language or a foreign language, interfered with comprehension of the film North by Northwest, relative to a control condition with no subtitles.…”
mentioning
confidence: 99%
“…A consistent pattern in the literature shows that younger audiences, regardless of their news-viewing habits, tend to be more successful than older generations at processing cluttered newscasts (Keefe-Feldman, 2007;Bergen et al, 2005). In contrast, Qihao et al (2014) found that women under the age of 30 were more likely to become overwhelmed with information than any other demographic.…”
Section: News Crawls Recall and Retentionmentioning
confidence: 91%
“…A natural corollary is that news crawls containing irrelevant or unstructured information could have a negative impact on retention of the on-screen story (Hargittai et al, 2012). Bergen et al (2005) used dual-coding to find that when confronted with media embedded with graphics, an individual will focus on the auditory elements more so than the visuals. With regard to the amount of non-reinforcing, extraneous information, Coffey and Cleary (2009) found that news networks also use crawls for self-promotion.…”
Section: News Crawls Recall and Retentionmentioning
confidence: 99%